3D Interactive Modeling of Pipe Failure in Water Supply Systems. (14th January 2021) - Dawood, Thikra; Elwakil, Emad; Novoa, Hector Mayol; Delgado, José Fernando Gárate
Abstract: The increased incidences of pipe breaks worldwide are posing a serious threat to potable water security in urban communities. The consequences may involve water loss and service interruptions, compromised water quality, infrastructure disruptions, and loss of revenue. Thus, creating failure assessment models is quite crucial to sustain water distribution networks (WDNs) and to optimize maintenance spending. This research paper aims at developing an assessment framework for water systems, as well as modeling the failure phenomena toward sustainable management of underground infrastructure. The city of El Pedregal in Peru was chosen to exemplify the methodology of the research due to the rapid pace of urbanization and growing economic activities in the region, which make water infrastructure even more critical. The framework is based on the application of modeling techniques stemming from statistical regression analysis (RA) and 3D schematic representation. First, the influential factors that lead to the deterioration of the WDNs are determined. Second, the RA technique is leveraged to evaluate and model the failure rate through consecutive simulation operations and a 3D surface plot. Finally, the efficacy of the model is investigated using different performance metrics, in conjunction with a residual analysis scheme. The validation results revealed the robustness of the model with R‐squared (R 2 ) and the sum of squares error (SSE) of 0.9767 and 0.0008, respectively. The developed model is a predictive tool that can be used by municipal engineers as a preemptive measure against future pipeline bursts or leaks.